Effects of Galla chinensis Extract on Growth Performance, Carcass Traits, Serum Antioxidation, Immune Function, and Gut Microbiota of Broilers - Yin, Xin; Ding, Peng; Xiao, Jian; Yang, Yanming; Song, Zehe; He, Xi; Zhang, Haihan (Frontiers in Animal Science, 2022)
Galla chinensis is an ancient Chinese medicine which is mainly used for healing diarrhea and wound bleeding. Its chemical components are mainly gallotannin and gallic acid with antibacterial, antiviral, antioxidant, anti-inflammatory, and neuroprotective functions in animals, thus promising to be a potential antibiotic substitute. In this study, a product of Galla chinensis extract (GCE) were supplemented for 360 broiler chickens in the diets with 0 mg/kg (Control), 250 mg/kg (GCE250), 500 mg/kg (GCE500) , 1000 mg/kg (GCE1000), 2000 mg/kg (GCE2000), plus 150 mg/kg aureomycin were added in feed as the antibiotic group. The experimental results showed that the low concentration of GCE supplementation (250 or 500 mg/kg) exhibited better outcome for broiler chickens than high dose GCE groups (1000 or 2000mg/kg) in total. Particularly, the birds in GCE250 group had higher final body weight (p< 0.05) compared with Control, which might be benefited by that the low dose supplementation of GCE significantly improved the broiler anti-oxidative and anti-inflammatory abilities by decreasing the serum levels of MDA, IL-6, and IFN-γ at day 60 (p< 0.05). Additionally, it was found that GCE supplementation apparently shifted the cecal microbiota of broiler chickens compared with Control at day 60 by PCoA clustering, and increased the relative abundance of beneficial bacterial genera such as Faecalibacterium, Parabacteroides, and Alistipes, while decreased the potential pathogenic bacteria Streptococcus. Taking together, dietary supplementation of low concentrations of GCE presented a positive influence on the growth performance, gut micrbiota, serum anti-oxidation and anti-inflammation. Therefore, the GCE may be promising to be developed as an antibiotic alternative for broiler production.